Investigation of in vitro genotoxic, cytotoxic, antiradical and phytochemical properties of endemic Verbascum diversifolium Hochst. - Keser, Serhat; Çiftçi, Ebru Bahar; Öz, Samet; Tekin, Suat; Kaygılı, Omer (Niyazi BULUT, 2025)
Verbascum species are consumed as tea among the public, and these species used as a breast softener, expectorant, in the treatment of hemorrhoids and rheumatism, and as a wound healer. To investigate the antiradical, cytotoxic, genotoxic and phytochemical compounds of ethanol, methanol and water extracts of endemic Verbascum diversifolium Hochst. (Nizip mullein) plant grown in Elazig is the main aim of this study. Antiradical activity of plant was determined against ABTS, DPPH and OH radicals, and cytotoxic and genotoxic activities were determined against human cancer cell lines of A2780 (ovarian) and MCF-7 (breast) with MTT and Comet assays. All extracts of V. diversifolium were in the ABTS radical scavenging test; V. diversifolium ethanol and methanol extracts in the DPPH radical scavenging test; V. diversifolium methanol extract in the OH radical scavenging test showed higher antiradical activity than the standard antioxidant BHT. This plant was determined to be rich in total phenolic, total flavonoid, total proanthocyanidin, ?-tocopherol, phytosterols and unsaturated fatty acids. DNA damage studies of V. diversifolium extracts were carried out by the Comet assay method using the parameters of the olive tail moment, tail density, tail length, head length and head density. The cell death occurred through the DNA damage mechanism, and it can be said that this plant shows effective cytotoxic activities.
Keywords: Biochemistry and Cell Biology (Other); Biyokimya ve Hücre Biyolojisi (Diğer)